Decision Support System for selecting study programs using the AHP method - Ramadhan, Dahfa; Marlinda , Linda (Politeknik Ganesha Medan, 2022)
In accordance with the curriculum that applies throughout Indonesia, prospective MA students who will register for a school will experience major selection (major). For this reason, prospective students are expected to be able to assess their interests, talents, and abilities so that they do not choose the wrong major to take. Many prospective students choose majors because of the influence of friends. The role of parents is very important. Parents should be able to direct their children to choose majors according to their interests, talents, and career opportunities. choosing a major while in MA will have an effect on continuing to the next college or career. Majors available include, IPA and IPS. Majors will be adjusted to the abilities, talents and interests of students. The formulation of the problem in the writing of this scientific paper is limited to the scope where many prospective students want to go there but do not know what major is suitable for them. The purpose of this study is to assist students in choosing major that is suitable for those who are only recommendations using the analytical hierarchy process method. The results of this study were found that the interest criteria had 0.42% or in percentage described 42%, a talent had 0.95% or in percentage described 95% and career opportunities had 0.47% or in achievement 47% in choosing majors